Exploring Proximal and Distal Psychosocial Stressors Influencing the Health Outcomes of Urban American Indians in the Midwest - (:unkn) unknown (My University, 2016)
Researchers have theorized that colonization and forced assimilation of American Indians/Alaska Natives (AI/AN) in the U.S. are associated with the current health outcomes of AI/AN groups. The literature has begun to link a number of negative health outcomes such as chronic illnesses, substance abuse, grief, depression, and anxiety with distal stressors associated with historical loss, as well as with proximal stressors that are continued reminders of historical trauma such as present day discrimination. The present study utilized a quantitative methodology along with a community informed framework through collaboration with multiple urban AI/AN-serving agencies in a metropolitan area of the Midwest to empirically study proposed theoretical models to explain health disparities in urban AI/AN adults. A paper-pencil self-report survey was provided to 285 voluntary adult participants. The measures gathered information about the participants’ thoughts and feelings relevant to historical loss, their involvement in health-promoting behaviors, current alcohol, commercial cigarette, and commercial smokeless tobacco use, and their perceptions of their experience being part of their cultural group and a minority within the United States. The results of this study document the prevalence of historical loss and its associated symptoms in a sample of urban AI/ANs adults living in the Midwest region of the U.S. The findings provide support for the impact of both the proximal stressor of perceived discrimination and the distal stressor of historical loss thoughts on the outcome of historical loss associated symptoms. Additionally, historical loss thoughts had a significant impact on cigarette use. No direct connection appeared to exist between historical loss thoughts and health-promoting behaviors, or between historical loss thoughts and alcohol use. Psychosocial variables of ethnic identity, mainstream comfort, and social affiliation did not appear to have a moderating influence between historical loss thoughts and historical loss associated symptoms. This study was funded by a community grant from Mayo Clinic’s Spirit of E.A.G.L.E.S. American Indian/Alaska Native Leadership Initiative on Cancer, a National Cancer Institute funded Special Populations Network. The project occurred in collaboration with an organization that provides employment and career services to AI/AN people living in the Southeastern region of a Midwest state. This project was informed by community feedback from AI/AN-serving organizations, including an urban Tribal agency, an urban AI/AN wellness consortium, and a regional inter-Tribal council. The de-identified aggregate results and findings will be disseminated with the appropriate community agencies and the funding program, for their use as they see fit. The findings from this project can potentially inform future health promotion work with local AI/AN organizations and urban AI/AN groups.
Keywords: American Indian/alaska Native; Discrimination; Health Disparities; Health Psychology; Historical Trauma; Minority Health